Pathogenic Variants of the PHEX Gene - Yasuhisa Ohata; Yasuki Ishihara (Endocrines, 2022)
Twenty-five years ago, a pathogenic variant of the phosphate-regulating endopeptidase homolog X-linked (PHEX) gene was identified as the cause of X-linked hypophosphatemic rickets (XLH). Subsequently, the overproduction of fibroblast growth factor 23 (FGF23) due to PHEX defects has been found to be associated with XLH pathophysiology. However, the mechanism by which PHEX deficiency contributes to the upregulation of FGF23 and the function of PHEX itself remain unclear. To date, over 700 pathogenic variants have been identified in patients with XLH, and functional assays and genotype–phenotype correlation analyses based on pathogenic variant data derived from XLH patients have been reported. Genetic testing for XLH is useful for the diagnosis. Not only have single-nucleotide variants causing missense, nonsense, and splicing variants and small deletion/insertion variants causing frameshift/non-frameshift alterations been observed, but also gross deletion/duplication variants causing copy number variants have been reported as pathogenic variants in PHEX. With the development of new technologies including next generation sequencing, it is expected that an increasing number of pathogenic variants will be identified. This chapter aimed to summarize the genotype of PHEX and related analyses and discusses the pathophysiology of PHEX defects to seek clues on unsolved questions.